2012
DOI: 10.3366/ijhac.2012.0046
|View full text |Cite
|
Sign up to set email alerts
|

Influences on children's visual cognition capabilities through playing ‘intelligent matrix’ developed by the augmented virtual reality technology

Abstract: In the development of young children's senses and action mobility, good visual cognition could help them with good habits of reading, writing, and logical learning. Digital teaching materials are common in use of enhancing the creativity and learning effects. Within them, the interacting manners and their influences on learning effects and learning attitudes lead to enhance the learning motivations and effects. The fun of game maintains a longer learning attention and advances the cognitive skills in easy mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Although it has been suggested that gender differences must be taken into consideration when developing educational tools (31), some previous game-based learning studies found no differences in outcomes related to gender (12,28). Other studies investigating the influences on children's visual cognition capabilities through playing with "intelligent matrix" with AR showed no difference by gender in performance (8). Robertson (31) found that female students had better retention of information than males because they use more time to write dialogues in the activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that gender differences must be taken into consideration when developing educational tools (31), some previous game-based learning studies found no differences in outcomes related to gender (12,28). Other studies investigating the influences on children's visual cognition capabilities through playing with "intelligent matrix" with AR showed no difference by gender in performance (8). Robertson (31) found that female students had better retention of information than males because they use more time to write dialogues in the activity.…”
Section: Discussionmentioning
confidence: 99%
“…Fun combined with learning becomes the appropriate solution if you want to captivate the attention of a child, as explained by the study called GoGoBox (Ho, Chung & Lin, 2012), which allows to deduce that the use of pedagogical tools improve creativity and the level of learning is greater; after applying this learning system it is obtained that the cognitive ability and the ability to memorise objects visually improves the apprehension of a certain subject.…”
Section: Applications Success Storiesmentioning
confidence: 99%
“…According to Chiong & Shuler (2010), a personalized and individual learning experience while using digital tools is one of the great opportunities to support the development of autonomy and independence. Ho, Chung, and Lin (2012) suggest that incorporating interactive visual elements into educational programs can improve learning motivation, attitudes, and accessibility. Children should be given the opportunity to choose and determine their own course of action.…”
Section: Introductionmentioning
confidence: 99%